ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU SEKS BEBAS PADA REMAJA - Rosena Maulida; Adiyat Syeh (CV. ADIBA AISHA AMIRA, 2025)
Free sex among adolescents is a growing and alarming phenomenon. This behaviour not only poses health risks, such as sexually transmitted diseases and unwanted pregnancies, but also has psychological and social impacts on adolescents. This study aims to analyse the factors that influence free sex among adolescents based on literature review and empirical studies. The factors examined include the influence of peers, social media, lack of sexual education, and family relationships. The results indicate that peer influence and access to sexual content on digital media are the primary triggers, while inadequate sexual education exacerbates the situation. Recommendations are provided for the active role of parents, schools, and the community in providing healthy education and supervision.